The Propensity to Consume - Gilboy, Elizabeth W. (Quarterly Journal of Economics, 1938)
I. The Distribution of Income, 121.— II. Statistical Evidence on the Relation between Income and Expenditure: the Brookings study, 123; Lough's study, 124; Zimmerman's findings, 125; the Consumer Purchase data for Chicago, Denver and Providence, 125; for villages in New England and the Middle West, 129; for small cities, 129; for farm operators, 134.— Data for occupational groups, 134.— Kaplan's analysis, 134.— Definition of savings, 135.— Inferences concerning Mr. Keynes' psychological law, 135.— III. The Psychological Basis, 138.— Conclusion, 140.